Evaluation of Field Training for Students of Special Education from the Perspective of Trainees and Supervisors: A Field Study at Princess Noura University - Sulaiman, Dr. Maha Abdullah AL (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at evaluating the status of field training at the department of special education, faculty of education, princess Noura University from the perspective of trainees and supervisors. To achieve the objectives of the study, the researchers designed two questionnaires: the first for trainees and the second for supervisors. The first one was applied to (141) students majoring in autism, learning difficulties, talent, and intellectual excellence. The second was applied to (20) supervisors specialized in autism and learning difficulties. After the data were statistically processed, the results relevant to the trainees revealed that they possess the suitable skills to apply what they learned in theory and also have the ability to benefit from technological devices in their classes. In addition, field training developed in them a positive attitude toward the teaching profession and provided them withself-confidence to teach individually or collectively. As for the most important challenges, they were: transportation from – to training places, absence of propitious educational aids in places of training, in addition extra work they were requested to do by school management and training centers. As for results pertaining supervisors, they revealed that training was needed for their self-development in the field of specialization. In addition, training made them teach theoretical courses in a more effective manner. The most challenging problems were found in: difficulty of performance in effecting duties in the theoretical courses set for them to teach and in the inadequate number of schools and training centers, besides absence of propitious educational aids in such schools and centers. The results also showed that specialization in learning difficulty was mostly affected by previously stated challenges if compared to those of autism and talent.